Ключові особливості нормативно-правової бази функціонування побратимських зв'язків міст України - Богородецька, Ольга Іванівна; Bohorodetska, Olha I. (Волинський національний університет імені Лесі Українки, 2012)
Проаналізовано правову основу функціонування побратимських зв’язків міст України, а також міжна-родно-правові документи, що визначають характер і спосіб формування зовнішніх зв’язків міст. Досліджено рівень розвитку муніципального права в Україні. Схарактеризовано рівні формування нормативно-правової бази функціонування побратимських зв’язків міст України. The legal basis of Ukraine’s cities’ twinning functioning is examined, legal international documents that determine the nature and way of cities’ external relations forming are analyzed. There is studied the level of development of municipal law in Ukraine. The levels of the forming of thelegal and regulatory base of Ukraine’s cities’ twinning functioning are analyzed.
The Key Features of the Legal and Regulatory Base of Ukraine’s Cities’ Twinning Functioning
Keywords: побратимські зв'язки; нормативно-правова база; міста-побратими; thelegal and regulatory base; twinning; twin-cities